Manajemen Kurikulum Tahfidz Qur’an Di Rumah Qur’an Al-Falaah Yasmin Bogor - Dede Ahmad Muhtarom; Joko Rustanto; Tri Yulianto; Wasto Wasto; Agus Triyantoz (Universitas Ibn Khaldun Bogor, 2022)
Tahfidzul Qur'an degradation is a process to maintain, maintain and preserve the purity of the Qur'an which was revealed to the Prophet sallallaahu 'Alaihi Wasallam by heart so that changes and falsifications do not occur and can guard against forgetfulness in whole or in part. Tahfidzul Qur'an is a method of reading the Koran that involves directly and practicing reading tartil according to the rules of recitation. This study uses a qualitative approach with descriptive methods that are supported through data collection techniques in the form of observation, interviews and documentation. Interviews were conducted with the Leader of the Al-Falaah Yasmin Bogor House of Qur'an and the person in charge of learning and the coordinator of the Banten branch of Tahfidzul Quran. Based on this research, the Tahfidzul Quran learning plan has been well conceptualized, because it has adopted the learning system in the central Tahfidzul Quran. In terms of organization, the implementation of Tahfidzul Qur'an has been carried out well. Implementation that involves all teaching staff and pesantren leaders in overseeing the implementation of this method of learning. The process of implementing learning in the classroom is carried out homogeneously according to the volume of each student. Controls that occur have been carried out in accordance with the objectives, vision, and mission to be achieved. This can be seen by the implementation of an evaluation in the form of an Evaluation of Tahfidzul Quran learning